2021
DOI: 10.1021/acs.jpclett.1c03077
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Half-Electron Self-Energy Correction for Fast and Accurate Nonadiabatic Molecular Dynamics

Abstract: The nonadiabatic (NA) process is crucial to photochemistry and photophysics and requires an atomistic understanding. However, conventional NA molecular dynamics (MD) for condensed-phase materials on the nanoscale are generally limited to the semilocal exchangecorrelation functional, which suffers from the bandgap and thus NA coupling (NAC) problems. We consider TiO 2 and a black phosphorus monolayer as two prototypical systems, perform NA-MD simulations of nonradiative electron−hole recombination, and demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…45 Our previous work has shown that the PBE-1/2 method can generate reasonable bandgaps and charge carrier lifetimes for BP and TiO 2 that are compared to those obtained from the hybrid functional but significantly reduce the computational cost. 44 The success stimulates the current work by using the PBE-1/2 method instead of a hybrid functional for leveraging the computational accuracy and efficiency. The method corrects the electron self-interaction term using the Slater half-occupation technique.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…45 Our previous work has shown that the PBE-1/2 method can generate reasonable bandgaps and charge carrier lifetimes for BP and TiO 2 that are compared to those obtained from the hybrid functional but significantly reduce the computational cost. 44 The success stimulates the current work by using the PBE-1/2 method instead of a hybrid functional for leveraging the computational accuracy and efficiency. The method corrects the electron self-interaction term using the Slater half-occupation technique.…”
mentioning
confidence: 94%
“…Then, we ran adiabatic MD simulation in the microcanonical ensemble with a 1 fs atomic time step to generate 25 ps trajectories. After that, the last 2000 geometries of these trajectories were chosen for calculating NA coupling using the PBE-1/2 correction method because this approach can lead to the correct bandgap . Finally, the Libra code was employed to simulate the nonradiative electron–hole recombination using the same geometries as the initial conditions …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But if the decoherence time is much smaller than the quantum transition time, a decoherence correction has to be induced. , A detailed description of the decoherence effect is provided in the Supporting Information. The methodology has been used to study photoexcitation dynamics in a wide range of systems, including metal oxides, perovskites, , interfacial systems, and so forth.…”
mentioning
confidence: 99%
“…Decoherence, by analogy to pure dephasing in nonlinear optical spectroscopy, has been included in the mixed quantum-classical NA-MD method. The method has been utilized in a variety of materials, , such as MAPbI 3 containing GBs interacting with O 2 or H 2 O , and experiencing compressive and tensile strain, two-dimensional perovskites, black phosphorus, , and transition-metal dichalcogenides …”
mentioning
confidence: 99%